“Examen especial a la cuenta bienes de larga duración y bienes administrativos no depreciables en la Dirección Distrital de Educación, responsable de la entidad operativa desconcentrada Dirección Provincial de Educación de Pichincha de la ciudad de Quito periodo del 1 de enero al 31 de diciembre del 2012 - Jácome Ortega, Blanca Ruth (2015)
The thesis "special account for Real Long-Lasting and Non-Depreciable Assets Administration at the District Education Office, Operational Entity responsible for Decentralized Management of Education Provincial Pichincha Quito period 1 January to 31 Review December 2012", it was developed as a contribution to the management of this institution and to meet a requirement prior to obtaining the title in Accounting and Auditing Accountant, Certified Public Auditor. Finally a report of more important tendinitis Special Consideration will be given to the authorities of the institution which will own opinions, conclusions and recommendations, in order to help strengthen the management of resources and secondly to present the aspects was developed to improve the system of internal control evaluation that help making the necessary corrections. For workof development the thesis research techniques were used to staff as necessary for the interview and timely information, which is analyzed by the internal control questionnaire to determine the reliability and fairness of their balances. Also proceeded to use the following methodology as the methods scientific, inductive, deductive, mathematical and analytical; that allowed to detect weaknesses in the same area examined the be evaluated, analyzed and described through narrative cedulas the decisions aimed at improving the institution. Upon completion of the Special Review was concluded that the Provincial Pichincha has not thoroughly examined this account no longer maintaining a real balance of goods that keeps the institution, that the computerized system is outdated, therefore it is recommended that a finding the state in which the property is situated and update the computerized system for rapid, timely and above all updated information